Passive leg movement in chronic obstructive pulmonary disease: evidence of locomotor muscle vascular dysfunction - Ives, Stephen J.; Layec, Gwenael; Hart, Corey R.; Trinity, Joel D.; Gifford, Jayson R.; Garten, Ryan S.; Witman, Melissa A. H.; Sorensen, Jacob R.; Richardson, Russell S. (Journal of applied physiology (1985), 2020)
Utilizing both the single and continuous passive leg movement (PLM) models, which induce nitric oxide (NO)-dependent hyperemia, this study provides evidence of vascular dysfunction in the locomotor muscle of patients with chronic obstructive pulmonary disease (COPD), independent of central hemodynamics. This impaired hyperemia may be the result of an oxidant-mediated attenuation in NO bioavailability. In addition to clearly dysfunctional lungs, vascular dysfunction in locomotor muscle may contribute to the exercise intolerance associated with COPD and increased cardiovascular disease risk. Chronic obstructive pulmonary disease (COPD), characterized by pulmonary dysfunction, is now also recognized to be associated with free radical-mediated vascular dysfunction. However, as previous investigations have utilized the brachial artery flow-mediated dilation technique, whether such vascular dysfunction exists in the locomotor muscle of patients with COPD remains unclear. Therefore, in patients with COPD ( n = 13, 66 ± 6 yr) and healthy age- and sex-matched control subjects ( n = 12, 68 ± 6 yr), second-by-second measurements of leg blood flow (LBF) (ultrasound Doppler), mean arterial pressure (MAP) (Finapres), and leg vascular conductance (LVC) were recorded before and during both 2 min of continuous upright seated continuous-movement passive leg movement (PLM) and a single-movement PLM (sPLM). In response to PLM, both peak change in LBF (COPD 321 ± 54, Control 470 ± 55 ∆mL/min) and LVC (COPD 3.0 ± 0.5, Control 5.4 ± 0.5 ∆mL·min −1 ·mmHg −1 ) were significantly attenuated in patients with COPD compared with control subjects ( P < 0.05). This attenuation in the patients with COPD was also evident in response to sPLM, with peak change in LBF tending to be lower (COPD 142 ± 26, Control 169 ± 14 ∆mL/min) and LVC being significantly lower ( P < 0.05) in the patients than the control subjects (COPD 1.6 ± 0.4, Control 2.5 ± 0.3 ∆mL·min −1 ·mmHg −1 ). Therefore, utilizing both PLM and sPLM, this study provides evidence of locomotor muscle vascular dysfunction in patients with COPD, perhaps due to redox imbalance and reduced nitric oxide bioavailability, which is in agreement with an increased cardiovascular disease risk in this population. This locomotor muscle vascular dysfunction, in combination with the clearly dysfunctional lungs, may contribute to the exercise intolerance associated with COPD. NEW & NOTEWORTHY Utilizing both the single and continuous passive leg movement (PLM) models, which induce nitric oxide (NO)-dependent hyperemia, this study provides evidence of vascular dysfunction in the locomotor muscle of patients with chronic obstructive pulmonary disease (COPD), independent of central hemodynamics. This impaired hyperemia may be the result of an oxidant-mediated attenuation in NO bioavailability. In addition to clearly dysfunctional lungs, vascular dysfunction in locomotor muscle may contribute to the exercise intolerance associated with COPD and increased cardiovascular disease risk.